Merleau-Ponty's Reading of Husserl
XXVI, 301 p.
Keywords: Merleau-Ponty's Reading of Husserl explores the relationship between two of the greatest thinkers of the twentieth century: Edmund Husserl, the father of modern phenomenology, and Maurice Merleau-Ponty, considered by many to be his greatest philosophical heir. While Merleau-Ponty's influence on the dissemination and reception of Husserl's thought is indisputable, unresolved questions remain concerning the philosophical projects of these two thinkers: Does phenomenology first reach its true potential in Merleau-Ponty's hands, guided by his appreciation of the tacit goals underlying Husserl's philosophical project? Or is Merleau-Ponty's phenomenology a creative but ultimately misdirected appropriation of Husserl's work? In this volume, the first devoted to a comparison of the work of these two philosophers, ten leading scholars draw on the latest research and newly available manuscripts to offer novel insights into Merleau-Ponty's reading of Husserl - with implications for our understanding of phenomenology's significance, its method, and the future of philosophy.